Refugee States : Critical Refugee Studies in Canada - Phu, Thy, 1975-; Nguyen, Vinh (Associate professor) (Book collections on Project MUSE., 2021)
"Exploring "refuge" and "refugee" as concepts that shape Canadian nation-building both within and beyond national borders, Refugee States takes an interdisciplinary and critical approach to describing how refugees articulate their relation to and defiance of official discourses. Through close examinations of refugee movements, contexts, and subjectivities, this collection reveals how Canada has relied upon the rejection and inclusion of refugees as a crucial means of statecraft. Bringing together renowned and emerging scholars from multiple disciplines, Nguyen and Phu illuminate the historical, political, and cultural conditions that produce refugees as well as the narrative of humanitarian benevolence that persists nationally and internationally. Highlighting landmark cases, the editors and contributors together develop critical refugee studies as a framework for understanding, nuancing, and critiquing the production of Canadian humanitarian exceptionalism--the international image and discourse of Canada as a liberal, tolerant, and welcoming haven for people fleeing oppression, persecution, and unfreedom. In doing so, Refugee States offers alternative modes of understanding past and present refugee passages to and within Canada, and brings to light the many ways in which refugee subjects navigate displacement, migration, and resettlement."--